Representasi Gaman pada Tokoh Kudou Chika dalam Anime Kono Oto Tomare - Khoirunnisa, Rafelia Anggita; Lusiana, Yusida; Puspitasari, Diana (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2024)
This research was conducted to determine the representation of gaman in the character Kudou Chika from the anime Kono Oto Tomare. This research is a qualitative descriptive study. The research data is in the form of scenes and dialog performed by the character Kudou Chika as a data source. The data collection methods used are library study techniques and observation and note-taking. The theory used in this research is semiotic theory by John Fiske which describes television codes through three levels, namely reality, representation, and ideology. From the results of the research, the representation of gaman is depicted through three characters owned by Kudou Chika, including persistent, patient and diligent. In addition, there are ideology of egoism and cultural nationalism in the anime Kono Oto Tomare.